Derivational Affixes in English and Arabic Words: The Process of Word Formation - Magvirah El Walidayni Kau (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This article discusses the process of derivational affixation in both English and Arabic. It aims to describe the affix derivation process, which results in changes in the meaning of some words attached by affixes. This is a qualitative research and all examples of words attached by affixes come from books, dictionaries, and other sources. The data collection results show that English and Arabic are very productive in the formation of new words when these words are attached by affixes, which can also cause changes in meaning. The obvious distinction between English and Arabic is in the root word. In Arabic, all basic words are verbs, whereas in English, the basic words that affixes can attach to are verbs, nouns, and adjectives.